Cabbage growers perception towards environmental and health safety in IPM adoption in the Cameron Highlands, Malaysia - Hussein, Md. Ariff; Radam, Alias; Mohd Amin, Hairuddin; Shamsudin, Mad Nasir (2008)
Perceptions on the importance of risk avoidance were found to vary depending on the impact category of environmental and health safety. The ranking of five impact categories according to the degree of importance was consistent across the three zones of respondents, starting with humans followed by farm animals, beneficial insects, fish and birds. The willingness to try more environmental friendly practices could have been motivated by their perceptions and beliefs about the harmful environmental impacts of pesticide use. The willingness to adopt alternative pest control practices such as reduced pesticide treatments, cabbage remove hull and pruning, mulching, and biological control was quite high among the farmers. This study showed that IPM programme would generate economic benefits that include improvements in water quality, food safety, pesticide application safety, and long term sustainability of pest management systems.